The Assessment of the White School Project Case study of ASEAN International Studies Kindergarten School drugs-free and mischief: The Assessment of the White School Project Case study of ASEAN International Studies Kindergarten School drugs-free and mischief - Charoonnimmarn, Tanaporn (RATANABUTH JOURNAL, 2024)
The objective is to evaluate the white school program of ASEAN International Studies Kindergarten School, Drugs-Free and mischief, according to CIPPIEST model. The assessment was carried out between July 16, 2022, and October 31, 2022. Evaluation form for the White School Program, ASEAN International Studies Kindergarten School, Drugs-Free and mischief. The overall assessment of the white school program, ASEAN International Studies Kindergarten School, Drugs-Free and mischief, had the highest level of quality. The benefit of this assessment makes an understanding of avoiding drugs and mischief, and the benefits of this assessment make them aware of information that reflects operational problems and obstacles. To utilize the planning and improvement of the operation to promote the quality of students of ASEAN International Studies Kindergarten School.